Tensile properties of a hybrid kenaf-glass fibre composite shaft - Zakaria, N.A.; Ishak, M.R.; Mustapha, F.; Yidris, N. (Elsevier, 2022)
Natural fibre derived from natural sources is another alternative to synthetic fibres to reinforce polymeric materials for the production of biocomposites. In this study, the effects of fibre orientation on kenaf fibre composite on tensile response were investigated. The hollow kenaf fibre composite shaft with 0celcius fibre orientation were fabricated using pultrusion method and 45celcius fibre orientation kenaf composite were fabricated using filament winding method. A better tensile strength was observed for the 0celcius fibre orientation. compared to the 45celcius orientation, with 39.16 MPa for the 0celcius orientation and 18.97 MPa for the 45celcius orientation. The kenaf fibre composite with a 0celcius fibre orientation was then formed into two compositions, a solid and hollow cylinder shaft. A glass fibre material has been used to strengthen the natural fibre in order to produce a hybrid solid composite shaft. The tensile properties of the hybrid shaft composite were found to be 96.29 % better than those of the kenaf shaft composite. Scanning electron microscopy (SEM) micrographs were used to analyse the failure mechanism and the adhesion between fibres. In conclusion, there is a great enhancement in mechanical properties of the hybridization forms of both kenaf and glass fibre.